2020
DOI: 10.1002/slct.202002627
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Oily Wastewater Using a Hyperbranched Poly (amido amine) Demulsifier with 1,4‐Phenylene Diamine as Central Core

Abstract: In the present study, a hyperbranched polymer demulsifier (PPDA) was synthesized by an improved “one‐pot” method with 1,4‐phenylene diamine as the central core, and ethylenediamine and methyl acrylate as the chain segments. NMR and Fourier transform infrared spectroscopy were used to confirm the molecular structure of the demulsifier, and thermogravimetric analysis was carried out to estimate its thermal stability. The effects of some important experimental parameters such as concentration, temperature and set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The hyperbranched polymer spray adjuvant (Po2) had a strong effect on reducing tension compared with vegetable oil, mixture, and others. Zhang et al [29] found that hyperbranched polymers can improve the wetting and spreading performance of solutions. Although other spray adjuvants can also play a role in reducing DST, their effects, compared with the above three spray adjuvants, were still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperbranched polymer spray adjuvant (Po2) had a strong effect on reducing tension compared with vegetable oil, mixture, and others. Zhang et al [29] found that hyperbranched polymers can improve the wetting and spreading performance of solutions. Although other spray adjuvants can also play a role in reducing DST, their effects, compared with the above three spray adjuvants, were still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbranched poly­(amido amine) demulsifiers have been widely reported, but most of these demulsifiers are used in diesel-in-water emulsions or oily wastewater, and a high temperature was needed. , In our recent work, the hyperbranched demulsifier with trimethyl citrate as the central core could demulsify only a diesel-in-water emulsion at ambient temperature . The hyperbranched polymer with 1,4-phenylene diamine as the centronucleus could break the oily wastewater, but the aqueous phase was not clear . It is reported that it is conducive to the demulsification when the central core structure of hyperbranched polymers is similar to the emulsifier structure .…”
Section: Introductionmentioning
confidence: 93%
“…The zeta potential of the original O/W emulsion is nearly −45.0 mV, indicating that the O/W emulsion is very stable. 24,35 The zeta potential of separated water changes dramatically after the PNDA-1 or PNDA-2 demulsifier was added to the O/W emulsion. The obvious change is that the zeta potential of aqueous phase gradually decreases with increasing concentration.…”
Section: Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the development of petroleum industry generates a large amount of oily wastewater (Fang et Typically, oil-water emulsion is fairly stable. It is stabilized by natural surface active substances (asphaltenes, waxes, and resins) and inorganic solids through the vigorous π-π interactions (Zhang et al 2020b). Furthermore, steric effect and electrostatic force can also affect the stability of oil-water emulsion (Ma et al 2020).…”
Section: Introductionmentioning
confidence: 99%